Penyuluhan dan Pendampingan Pembukuan Sederhana Pada UMKM Tahu Tempe Pantura di Desa Tegalrejo - Diya Ayu Rahmawati; Siti Ning Farida (BADAN PENERBIT STIEPARI PRESS, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses run by small people with limited capital and applying fairly simple technology. One of the UMKM in Tegalrejo Village is Pak Sugik's UMKM Tahu Tempe